Electron-Impact Ionization of Atomic Ions: Theoretical Results - YUMAK YAHŞİ, AYŞE; YAVUZ, İLHAN; ALTUN, ZİKRİ (IOP PUBLISHING LTD, 2009)
A brief overview is given of theoretical results for electron-impact ionization of atoms and ions. A description is given of the main theoretical methods, along with the databases where the data are archived. It is shown that for light species, ground and metastable ionization cross sections are in reasonable agreement with experiment when non-perturbative data are used for the near neutrals and distorted wave data are used for ions greater than a few times ionized. Some discrepancies between theory and experiment still remain for systems with open d and open p subshells. The sensitivity of ionization rate coefficients to the near threshold part of the ionization cross section is shown. The role of excited states in effective ionization rate coefficients is demonstrated and recent excited state ionization cross section results for H, He, He+, B2+ and Ne are presented.
Keywords: COLLISIONAL-RADIATIVE MODEL; ABSOLUTE CROSS-SECTIONS; OPTICALLY THIN PLASMAS; RARE-GAS ATOMS; RATE COEFFICIENTS; HYDROGEN SCATTERING; LEVEL POPULATIONS; LIGHT-ELEMENTS; EXCITED-STATES; RECOMBINATION